A review and update of the corrugated fibreboard cushioning. Issue 9 (10th May 2022) - Ge, Changfeng
Abstract : The corrugated fibreboard was the dominated cushioning material before the advent of expanded plastic foams in the 1960s. With recent advances in packaging sustainability, the corrugated pads are again the research focus. This paper reviewed studies of corrugated fibreboard cushioning in areas of design and experimental evaluation. Since most of these research works were performed more than half a century ago, the historical data were reexamined and compared with the current practices. Previous and recent structure designs, represented by layered corrugated pads, tube, spring and zig‐zag components, were displayed and discussed. This study also reviewed studies investigating the crush resistance and cushion curves in hope to provide some practical guidance on prediction of cushioning performance. As an updated development by the author, this study presented cushion curves developed under three loading patterns, namely, column, underhang and overhang. Finally, the study pointed out that double dipping points and shift‐to‐right tendency on the cushion curves, as well as the long plateau on the stress–strain curves, are unique properties of corrugated fibreboard cushioning. Packaging engineers are suggested to factor in these properties in design for different applications. Abstract : The corrugated fiberboard was the dominated cushioning material before the advent of expanded plastic foams in the 1960s. With recent advances in packaging sustainability, the corrugated pads are again the research focus. This paper reviewed studies of corrugated fiberboard cushioning in areas of design and experimental evaluation.